The Effect of Training on Employee Performance with Work Discipline as Mediating Variable at PT. PLN (Persero) - Fesanlau, Murni Ariyani; Yuliati, Uci; Febriani, Rizki (Universitas Muhammadiyah Malang, 2024)
This study aims to examine the effect of training on employee performance mediated by work discipline. This study uses a quantitative and descriptive approach, with the PLS-SEM approach. The object of this research is PT. PLN (PERSERO) UP3 Jayapura with a population and sample of 70 employees. Data were analyzed using SmartPLS version 3.0 software. The results of this study indicate that Training has a significant effect on employee performance. Training has a significant effect on work discipline. Work discipline has a significant effect on employee performance. Work discipline can mediate between training and employee performance in full, which means that work discipline can strengthen the effect of training in improving employee performance.